Fetuin-A 742 (C/T) and 766 (C/G) polymorphic sites are associated with increased risk of myocardial infarction in older patients (40 years of age) - Çoker Gürkan, Ajda; Palavan Ünsal, Zeynep Narçın; ARISAN, ELİF DAMLA; GENÇ, SELMA; YERLİKAYA, PINAR OBAKAN; COŞKUN, DENİZ (Spandidos Publ Ltd, Pob 18179, Athens, 116 10, Greece, 2015)
Inflammation and genetics have key roles in the pathogenesis of atherosclerosis, and the etiology of myocardial infarction (MI). Recent studies have indicated that lower serum levels of fetuin-A may accelerate the vascular mineralization process, which leads to pathophysiological conditions, such as coronary heart disease and chronic renal failure. The aim of the present study was to evaluate the association between specific fetuin-A polymorphisms (742 and 766) that are associated with circulating serum levels, and MI cases. The study consisted of 292 participants; 146 healthy control subjects and 146 patients with MI. The patient group was divided into two subgroups: 56 MI40 years and 90 MI40 years. The genotype distribution of fetuin 742 (C/T) and fetuin 766 (C/G) were determined by restriction enzyme digestion of polymerase chain reaction products. A significant difference was determined between the patients with MI and the control subjects with regards to fetuin-A 742 C/T gene polymorphism (P=0.028), regardless of age. Genotype distributions of fetuin-A 742 (C/G, P= 0.004) and 766 (C/T, P=0.017) were statistically different in the older patients with MI (MI40 years old), as compared with the healthy controls; however, there were no significant differences between the younger patients with MI and the controls, with regards to fetuin-A 742 C/T (P=0.519) and 766 C/G (P=0.653) gene polymorphisms. In addition, an association was observed between the presence of fetuin-A 742 T and 766 G alleles, and MI cases. The present study demonstrates that fetuin-A 742 (C/T) and 766 (C/G) genotypes may be risk factors for MI in patients older than 40 years of age.
Keywords: Fetuin-A; Myocardial infarction; Single nucleotide polymorphisms; Alpha(2)-Heremans-Schmid Glycoprotein/Fetuin-A; Coronary-artery calcification; Unstable angina; Cardiovascular-diseases; Gene polymorphisms; Heart-disease; Global burden; Serum; Ahsg